Stomatal rings: structure, functions and origin. (8th December 2020) - Pautov, Anatoly; Bauer, Svetlana; Ivanova, Olga; Krylova, Elena; Yakovleva, Olga; Sapach, Yulia; Pautova, Irina
Abstract: Stomatal rings are structural elements of stomata of some flowering plants, being found in various groups of eudicots. The presence of a stomatal ring on a stoma does not depend on stomatal complex types, dimensions of stomata or their density. The guard cells of these stomata lie on the subsidiary cells. The location of the outer ledges on the outer tangential walls of the guard cells and the position of the stomatal rings on the guard cell walls around the outer ledges or on the outer ledges themselves are also among the characteristic features of these stomata. To elucidate the role of the stomatal rings we applied modelling using the finite-element method. The modelling has shown that the outer ledges prevent movements of the outer tangential walls of the guard cells and stimulate movements of the inner tangential walls and the immersion of the opening stomatal pore in the epidermis. Stomatal rings can enhance this effect. They also prevent the movements of the outer ledges and the widening of the stomatal aperture between them during stoma opening. This type of stomata occurs in evergreen plants growing in diverse conditions.